Content Analysis of Comparative Advertisements - Ashok Kumar, Sukanya (Indian Journal of Marketing, 2005)
Comparative Advertisement is a form of advertising in which two or more named, recognizable brands of the same product class are compared and the comparison is made in terms of one or more attributes. In USA, the use of comparative advertising was made legal in 1971, when Federal Trade Commission not only legalized it, but also encouraged advertisers to provide more comparative information (to enable consumers to take better decisions) through the use of such advertisements. Since then, advertisements with comparative format have been increasingly used and their effectiveness as compared to the non comparative advertisements has also been extensively researched. Other aspects like the ethicality of advertisements with such format; the views of the advertisers, advertisement agencies, consumers and regulators have also been topics of interest for researchers.